If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y = (-7/4)*x-3 // - (-7/4)*x-3
y-((-7/4)*x)+3 = 0
(7/4)*x+y+3 = 0
7/4*x+y+3 = 0 // - y+3
7/4*x = -(y+3) // : 7/4
x = (-(y+3))/7/4
x = -4/7*(y+3)
x = -4/7*(y+3)
| 37c=777 | | y=7/5x+7 | | 2x-(4-2x)=-3(2-x) | | F(x)=2x^2-3x+1 | | f(x)=3(4)x-4 | | 3x-9=(-4) | | y=9/10x | | X(5x-15)=0 | | y=0.9x | | 0.5x-18=2 | | 4-7a=-24 | | F(x)=-2x^2+3x-1 | | 4-7a=24 | | y=-0.428x | | 3x^2-11x+3=-3 | | 4.34+.793+6= | | 13=4x-7 | | x/3-2=3x/5 | | 36b^2-12b+1=0 | | 8x/9=5/6 | | y=-3/7x | | z^2-(1+4i)z-5+5i=0 | | y=-.042x | | x^2+9x=70 | | 2+4+6+8+10+2n=27 | | 6b+6=4b | | 2+4+6+8+2n=27 | | 2x^2-1/2x=1/8 | | (42/2+60-8)+(61-8*3) | | 6g=-7+5g | | 8x+3=x-15 | | 1+3+5+7+9+(2n-1)=26 |